Peningkatan Hasil Belajar IPAS Menggunakan Model Kooperatif Tipe Think Pair Share di Kelas V SDN 22 Kampung Luar Salido - Ardia, Desi Fitri; Hamimah, Hamimah (Universitas Negeri Padang, 2025)
This research was motivated by the low integrated thematic learning outcomes of class V students at SDN 22 Kampung Luar Salido. The research results showed that the teaching module for cycle I obtained an average of 83.33% (B), increasing in cycle II to 91.66% (SB). The results of the implementation of teacher activity learning in cycle I obtained an average of 80% (B), increasing in cycle II to 95% (SB). The results of the implementation of learning activities for students in cycle I obtained an average of 80% (B), increasing in cycle II to 95% (SB). The results of the attitude assessment in cycle I obtained 11 students who stood out, namely 6 people who had a positive attitude and 5 people who had a negative attitude, then in cycle II, 5 people who stood out had a positive attitude. The assessment of knowledge and skills in cycle I obtained an average of 74.5 (C), increasing in cycle II to 86.82 (B). Thus, it can be concluded that the think pair share (TPS) type cooperative model can improve student learning outcomes in science and technology learning in class V of SDN 22 Kampung Luar Salido, Pesisir Selatan Regency.